Bolivian Rhinotragini III: new genera and species (Coleoptera, Cerambycidae) - Clarke, Robin O.S. (Papéis Avulsos de Zoologia, 2010)
Bolivian Rhinotragini III: new genera and species (Coleoptera, Cerambycidae). Three new genera are described: Anomalotragus with two new species, A. recurvielytra and A. morrisi; Antennommata with one new species, A. costata; and Stultutragus with two new species, S. mataybaphilus and S. crotonaphilus, five transferred from Ommata (Eclipta) Bates, 1873, S. fenestratus (Lucas, 1857) comb. nov., S. poecilus (Bates, 1873) comb. nov., S. xantho (Bates 1873) comb. nov., S. bifasciatus (Zajciw, 1965) comb. nov., and S. cerdai (Peñaherrera-Leiva & Tavakilian, 2003) comb. nov., and one transferred from Cantharoxylymna Linsley, 1934, S. linsleyi (Fisher, 1947) comb. nov. Other new species described are: Ommata (Ommata) buddemeyerae, Ommata (Chrysaethe) amboroensis and Neoregostoma bettelai. Both sexes of Ommata (Ommata) quinquemaculata Zajciw, 1966 and Pseudagaone suturafissa Tippmann, 1960 are redescribed, and one species transferred from Neoregostoma Monné & Giesbert, 1992, Pseudagaone cerdai (Tavakilian & Peñaherrera-Leiva, 2007) comb. nov. All the Bolivian species are illustrated and host flower records provided.